Spherical silicon-carbon composite material as well as preparation method and application thereof
Spherical silicon-carbon composite materials are formed through spray drying technology, which solves the problems of morphology and structural regulation of nano-silicon carbon materials, improves the dynamic performance and cycle stability of lithium-ion batteries, and meets the needs of high energy density.
Patent Information
- Application Number
- CN202411065757.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-05
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-08-05
AI Technical Summary
The prior art cannot accurately regulate the morphology and structure of nano-silicon carbon materials, resulting in insufficient dynamic performance and cyclic stability of lithium-ion batteries, which cannot meet the needs of high energy density.
Spray drying technology is used to systematically stir and mix the silicon source and graphite to form a spherical structure made of graphite sheets stacked, and nano-silicon is combined on the surface of the graphite layer, and conductive agents and binders are added to improve the conductivity and close bond of the material. .
The spherical silicon-carbon composite material prepared by this method significantly improves the kinetic performance and cycling stability of lithium-ion batteries, reduces the risk of damage to the electrode structure by volume expansion of silicon, and improves the first Coulomb efficiency and capacity retention rate.
Smart Images

Figure CN119153642A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to a spherical silicon-carbon composite material and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries have the advantages of high energy density, environmental friendliness, and long cycle life. They have been widely used in energy storage fields such as electric vehicles and smart phones. With the increasing demand for these electronic products, people have put forward higher requirements for the energy density of batteries. my country aims to achieve a battery cell density of 400Wh / Kg in 2025 and strive to reach 500Wh / Kg in 2030. However, the specific capacity of traditional graphite anodes has reached its theoretical limit, and the energy density is greatly limited. The extremely high theoretical specific capacity (4200mAh / g), high safety, and relatively low and flat working potential of silicon-based anodes make them the most promising anode materials. However, silicon-based anodes have poor electronic conductivity and large volume expansion (>300%) during charging and discharging, which leads to the pulverization of active materials and the destruction of electrode structure, resulting in rapid attenuation of battery capacity.
[0003] To overcome these problems, silicon particles can be refined to the nanoscale, shortening the diffusion path of lithium ions and alleviating the volume expansion effect. Carbon materials such as graphite have higher conductivity and rate performance. Therefore, the nano-silicon-carbon material formed by the composite of the two combines the advantages of both and has a high industrialization prospect.
[0004] In addition, the design of the morphology and structure of nano-silicon carbon materials is also a focus of research. Studies have shown that spherical nano-silicon carbon materials can alleviate the accumulation of local stress generated by silicon during expansion, shorten the diffusion distance of lithium ions, and improve the dynamic properties of nano-silicon carbon materials. However, the existing technologies, conventional sand milling, carbon coating and other processes cannot accurately control the morphology and structure of nano-silicon carbon materials. The control of spherical morphology and appropriate structural design are barriers that we need to overcome.
[0005] Therefore, the prior art still needs to be improved and developed. Summary of the invention
[0006] In view of the above-mentioned deficiencies in the prior art, the present invention provides a spherical silicon-carbon composite material and a preparation method and application thereof, so as to solve the problem that the existing preparation method cannot accurately control the morphology and structure of nano-silicon-carbon materials.
[0007] The technical solution adopted by the present invention to solve the above technical problems is as follows:
[0008] A first aspect of the present invention provides a method for preparing a spherical silicon-carbon composite material, the preparation method comprising the following steps:
[0009] Dissolving a binder in a first solvent and performing a first stirring process to obtain a first stirred product;
[0010] adding graphite to the first stirred product, and performing a second stirring process to obtain a second stirred product;
[0011] adding a silicon source, a second solvent and a conductive agent to the second stirred product, and performing a third stirring treatment to obtain a third stirred product;
[0012] The third stirred product is subjected to spray drying treatment to obtain the spherical silicon-carbon composite material, wherein the spherical silicon-carbon composite material includes a spherical structure formed by stacking graphite sheets and silicon bonded to the surface of the spherical structure.
[0013] Preferably, the step of dissolving the binder in the first solvent and performing a first stirring treatment to obtain the first stirred product is specifically: adding the first solvent and the binder into a vacuum stirring kettle, setting the parameters of the vacuum stirring kettle, performing a first stirring treatment, the time of the first stirring treatment is 5-150 minutes, and obtaining the first stirred product;
[0014] Wherein, the parameters of the vacuum stirring kettle include: stirring speed of 20-60rpm, dispersion speed of 300-3000rpm.
[0015] Preferably, the step of adding graphite to the first agitant and performing a second stirring treatment to obtain a second agitant comprises: adding graphite to a vacuum stirring kettle containing the first agitant, setting parameters of the vacuum stirring kettle, performing a second stirring treatment, wherein the time of the second stirring treatment is 5-150 minutes, to obtain a second agitant;
[0016] Wherein, the parameters of the vacuum stirring kettle include: stirring speed of 20-60rpm, dispersion speed of 300-3000rpm.
[0017] Preferably, the step of adding a silicon source, a second solvent and a conductive agent to the second agitant and performing a third stirring treatment to obtain a third agitant comprises: adding a silicon source, a second solvent and a conductive agent to a vacuum stirring kettle containing the second agitant, setting parameters of the vacuum stirring kettle, performing a third stirring treatment, wherein the time of the third stirring treatment is 5-150 minutes, to obtain a third agitant;
[0018] Wherein, the parameters of the vacuum stirring kettle include: stirring speed of 20-60rpm, dispersion speed of 300-3000rpm.
[0019] Preferably, the parameters of the spray drying process are: inlet temperature of 100-300°C, outlet temperature of 60-120°C, atomizing disk speed of 150-300 Hz, and fan frequency of 15-40 Hz.
[0020] Preferably, in the third mixture, the mass ratio of graphite to silicon source is (3-8): (3-6), the mass ratio of graphite to binder is (95-100): (1-5), and the mass ratio of graphite to conductive agent is (95-100): (1-5).
[0021] Preferably, the silicon source is selected from one of nano-silicon, micron-silicon, and porous silicon, the binder is selected from one of CMC binder, PVDF binder, and PMMA binder, the conductive agent is selected from one of carbon nanotubes, conductive carbon black, and graphene, the first solvent is selected from one of water, alcohol, and methanol, and the second solvent is selected from one of water, alcohol, and methanol.
[0022] Preferably, the first stirring process, the second stirring process and the third stirring process are all repeated at least twice.
[0023] A second aspect of the present invention provides a spherical silicon-carbon composite material, the spherical silicon-carbon composite material comprising a spherical structure formed by stacking graphite sheets and silicon bonded to the surface of the spherical structure;
[0024] And / or, the spherical silicon-carbon composite material is prepared by the above-mentioned preparation method.
[0025] The third aspect of the present invention provides the use of the above-mentioned spherical silicon-carbon composite material in the preparation of lithium-ion batteries.
[0026] Beneficial effects:
[0027] The present invention discloses a spherical silicon-carbon composite material and a preparation method and application thereof. The method of the present invention first systematically stirs and mixes a silicon source and graphite, and then obtains a spherical silicon-carbon composite material by spray drying technology. The spherical silicon-carbon composite material prepared by the present invention is formed by stacking flaky graphite (graphite layer), and silicon is combined on the surface of the graphite layer to form a spherical structure of silicon-coated graphite. There are certain gaps between the graphite layers, which provide space for the volume expansion of silicon, and the graphite layer is combined with nano-silicon, which shortens the diffusion distance of lithium ions. The combination of the two is very tight, which is beneficial to the dynamic performance of lithium-ion batteries. In addition, the present invention adds a conductive agent and a binder when the silicon source and graphite are mixed. The binder ensures the close combination of the two. The presence of the conductive agent and the graphite layer greatly improves the conductivity of lithium ions, thereby improving the diffusion dynamics. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1This is a SEM image of the spherical silicon-carbon composite material prepared in Example 1 of the present invention;
[0029] Figure 2 The XRD pattern of the spherical silicon-carbon composite material prepared in Example 1 of the present invention;
[0030] Figure 3 The Raman spectrum of the spherical silicon-carbon composite material prepared in Example 1 of the present invention;
[0031] Figure 4 The first cycle charge-discharge curves of the spherical silicon-carbon composite material, graphite and pure silicon prepared in Examples 1-4 of the present invention;
[0032] Figure 5 The cycle performance and electrode expansion rate of the spherical silicon-carbon composite material, graphite and pure silicon prepared in Examples 1-4 of the present invention in the first 100 cycles. DETAILED DESCRIPTION
[0033] The present invention provides a spherical silicon-carbon composite material and a preparation method and application thereof. In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0034] An embodiment of the present invention provides a method for preparing a spherical silicon-carbon composite material, the preparation method comprising the following steps:
[0035] Dissolving a binder in a first solvent and performing a first stirring process to obtain a first stirred product;
[0036] adding graphite to the first stirred product, and performing a second stirring process to obtain a second stirred product;
[0037] adding a silicon source, a second solvent and a conductive agent to the second stirred product, and performing a third stirring treatment to obtain a third stirred product;
[0038] The third stirred product is subjected to spray drying treatment to obtain the spherical silicon-carbon composite material, wherein the spherical silicon-carbon composite material includes a spherical structure formed by stacking graphite sheets and silicon bonded to the surface of the spherical structure.
[0039] The embodiment of the present invention first systematically stirs and mixes the silicon source and graphite, and then obtains a spherical silicon-carbon composite material by spray drying technology. The spherical silicon-carbon composite material prepared by the present invention is composed of stacked flaky graphite (graphite layer), and silicon is combined on the surface of the graphite layer to form a spherical structure of silicon-coated graphite. There are certain gaps between the graphite layers, which provide space for the volume expansion of silicon, thereby reducing the probability of material rupture and pulverization, and the graphite layer is combined with nano-silicon, which increases the contact area between silicon and the graphite layer and shortens the diffusion distance of lithium ions. The combination of the two is very close, which is beneficial to the dynamic performance of lithium-ion batteries. The presence of graphite can also greatly improve the conductivity of the silicon-carbon composite material, greatly improving the first coulomb efficiency and cycle stability.
[0040] The embodiment of the present invention also adds a conductive agent and a binder when the silicon source and graphite are mixed. The binder can ensure the close compound between silicon and graphite, prevent silicon from falling off the graphite, and make the overall structure more solid. The conductive agent can further increase the conductivity of the silicon-carbon composite material.
[0041] Moreover, even if silicon expands and breaks during the cycling of lithium-ion batteries, the detached silicon can refill the gaps between graphite layers, thus ensuring good electrical contact and excellent capacity.
[0042] In some embodiments, the step of dissolving the binder in the first solvent and performing a first stirring treatment to obtain a first agitated product is specifically as follows: adding the first solvent and the binder to a vacuum stirring kettle, setting the parameters of the vacuum stirring kettle, performing a first stirring treatment, wherein the time of the first stirring treatment is 5-150 minutes, to obtain a first agitated product;
[0043] Wherein, the parameters of the vacuum stirring kettle include: stirring speed of 20-60rpm, dispersion speed of 300-3000rpm.
[0044] In some embodiments, the step of adding graphite to the first agitant and performing a second stirring treatment to obtain a second agitant is specifically: adding graphite to a vacuum stirring kettle containing the first agitant, setting the parameters of the vacuum stirring kettle, performing a second stirring treatment, the time of the second stirring treatment is 5-150 minutes, and obtaining a second agitant;
[0045] Wherein, the parameters of the vacuum stirring kettle include: stirring speed of 20-60rpm, dispersion speed of 300-3000rpm.
[0046] In some embodiments, the step of adding a silicon source, a second solvent and a conductive agent to the second agitant and performing a third stirring treatment to obtain a third agitant is specifically: adding a silicon source, a second solvent and a conductive agent to a vacuum stirring kettle containing the second agitant, setting the parameters of the vacuum stirring kettle, performing a third stirring treatment, and the time of the third stirring treatment is 5-150 minutes to obtain a third agitant;
[0047] Wherein, the parameters of the vacuum stirring kettle include: stirring speed of 20-60rpm, dispersion speed of 300-3000rpm.
[0048] In some embodiments, the parameters of the spray drying process are: inlet temperature of 100-300°C, outlet temperature of 60-120°C, atomizing disk rotation speed of 150-300 Hz, and fan frequency of 15-40 Hz.
[0049] In some embodiments, in the third mixture, the mass ratio of graphite to silicon source is (3-8): (3-6), the mass ratio of graphite to binder is (95-100): (1-5), and the mass ratio of graphite to conductive agent is (95-100): (1-5). At this mass ratio, the capacity advantage of nano-silicon and the cycle stability advantage of graphite can be maximized, and the close bonding and high conductivity between nano-silicon and graphite are also guaranteed. The binder can tightly bind graphite and nano-silicon to ensure that nano-silicon does not fall off from graphite, and the conductive agent can solve the problem of low conductivity of silicon and improve conductivity. If the nano-silicon content is too high, the material cycle stability is too poor and the capacity decay is serious; if the graphite content is too high, the material capacity is too low. If the ratio of conductive agent to binder is too low, the nano-silicon will easily fall off the graphite and fail, and the material conductivity is too low; if the ratio of conductive agent to binder is too high, the gram capacity of nano-silicon carbon material will be reduced, and the capacity properties will not be fully utilized.
[0050] In some preferred embodiments, in the third mixture, the mass ratio of graphite to silicon source is 1:1, the mass ratio of graphite to binder is 100:1, and the mass ratio of graphite to conductive agent is 100:1.
[0051] In some embodiments, the silicon source is selected from one of nano-silicon, micron-silicon, and porous silicon, the binder is selected from one of CMC binder, PVDF binder, and PMMA binder, the conductive agent is selected from one of carbon nanotubes, conductive carbon black, and graphene, the first solvent is selected from one of water, alcohol, and methanol, and the second solvent is selected from one of water, alcohol, and methanol.
[0052] The embodiment of the present invention preferably uses nano silicon as the silicon source. Compared with other silicon particles of larger size, nano silicon has stronger mechanical strain capacity and lower cracking degree. Nano silicon particles have a larger specific surface area. Nano-structuring of silicon materials can buffer the volume expansion of silicon-based negative electrodes.
[0053] In some embodiments, the first stirring process, the second stirring process, and the third stirring process are all repeated at least twice.
[0054] The embodiment of the present invention further provides a spherical silicon-carbon composite material, the spherical silicon-carbon composite material comprising a spherical structure formed by stacking graphite sheets and silicon bonded to the surface of the spherical structure;
[0055] And / or, the spherical silicon-carbon composite material is prepared by the above-mentioned preparation method.
[0056] The embodiment of the present invention provides the use of the above-mentioned spherical silicon-carbon composite material in the preparation of lithium-ion batteries.
[0057] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments, and are only for illustrating the present invention but not limiting the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0058] Example 1
[0059] A preparation method of a spherical silicon-carbon composite material comprises the following steps:
[0060] (I) Dispersion process
[0061] (1) 1125 g of pure water was added to a vacuum stirred kettle, and then 5.2 g (1.0%) of binder CMC powder was added; 1.0% is the solid content of CMC;
[0062] (2) Set the stirring speed to 40 rpm and the dispersion speed to 500 rpm, and stir and disperse for 10 min. After the end, open the stirring kettle and scrape off the CMC stuck on the mixer. Repeat twice;
[0063] (3) Close the stirring kettle and evacuate the mixture;
[0064] (4) Set the stirring speed to 60 rpm and the dispersion speed to 2000 rpm, and stir and disperse for 60 min. After the end, open the stirring kettle and scrape off the CMC stuck on the stirrer;
[0065] (5) Take 250 g of graphite and add it to the above stirring tank;
[0066] (6) Set the stirring speed to 40 rpm and the dispersion speed to 500 rpm, and stir and disperse for 10 minutes. After the end, open the stirring kettle and scrape off the graphite stuck on the stirrer. Repeat twice;
[0067] (7) Set the stirring speed to 60 rpm and the dispersion speed to 1500 rpm, and stir and disperse for 120 min. After the end, open the stirring kettle and scrape off the slurry stuck on the stirrer;
[0068] (8) Add 250g of Zhongning silicon and 250g of alcohol into a stirred tank;
[0069] (9) adding 0.5 g (0.1%) or 125 g (0.4%) of single-walled carbon nanotube slurry;
[0070] (10) Set the stirring speed to 40 rpm and the dispersion speed to 500 rpm, and stir and disperse for 10 min. After the end, open the stirring kettle and scrape off the CMC stuck on the mixer. Repeat twice;
[0071] (11) Set the stirring speed to 60 rpm and the dispersion speed to 1500 rpm. Stir and disperse for 120 min. After the stirring is completed, open the stirring kettle and scrape off the slurry stuck on the stirrer.
[0072] (II) Spraying process
[0073] (1) Pre-spray preparation - oxygen removal and temperature increase;
[0074] (2) Pour the mixed solution of the dispersed graphite and silicon into a spray apparatus.
[0075] (3) Set the spray parameters: inlet temperature: 200°C, outlet temperature: 90°C, atomizing disk speed: 250 Hz, fan frequency: 25 Hz.
[0076] (4) After 15 seconds, a spherical silicon-carbon composite material is obtained.
[0077] Example 2
[0078] A preparation method of a spherical silicon-carbon composite material. The method of this embodiment is basically the same as that of Example 1, except that the amount of graphite used is 450g, the amount of Zhongning silicon used is 50g, and the ratio of graphite to Zhongning silicon is 9:1.
[0079] Example 3
[0080] A spherical silicon-carbon composite material is prepared. The method of this embodiment is basically the same as that of embodiment 1, except that the amount of graphite used is 400 g, the amount of Zhongning silicon used is 100 g, and the ratio of graphite to Zhongning silicon is 8:2.
[0081] Example 4
[0082] A preparation method of a spherical silicon-carbon composite material. The method of this embodiment is basically the same as that of Example 1, except that the amount of graphite used is 350g, the amount of Zhongning silicon used is 150g, and the ratio of graphite to Zhongning silicon is 7:3.
[0083] Performance testing experiment
[0084] (1) The spherical silicon-carbon composite material prepared in Example 1 was characterized by SEM scanning electron microscopy. The results are as follows Figure 1 As shown: the overall morphology of the product is a sphere, and the sphere is composed of stacked flaky graphite. There are certain gaps between the graphite layers, which provides space for the volume expansion of nano-silicon. Nano-silicon is evenly bonded to the graphite layer to form a spherical structure of nano-silicon coated graphite, shortening the diffusion distance of lithium ions. The two are closely combined, which is beneficial to the kinetic performance of lithium-ion batteries.
[0085] (2) XRD and Raman characterization were performed on the spherical silicon-carbon composite material prepared in Example 1. The results are as follows: Figure 2 and 3 As shown: Its XRD diffraction peaks are exactly consistent with the standard PDF cards of graphite and silicon. From the Raman spectrum, it can be seen that at 500cm -1 There is an extremely strong crystallization peak at the center, which corresponds to the Raman spectrum of nanosilicon.
[0086] (3) The electrochemical characterization of the spherical silicon-carbon composite materials with different silicon-carbon ratios of Examples 1-4 was carried out. Table 1 below shows the first cycle coulombic efficiency and first cycle charge specific capacity of the spherical silicon-carbon composite materials with silicon-carbon ratios of 1:9, 2:8, 3:7, and 5:5, respectively, and pure silicon and graphite in the voltage range of 0.005-1.5V;
[0087] Table 1
[0088]
[0089] Figure 4The first cycle charge and discharge curves of spherical silicon-carbon composite materials with silicon-carbon ratios of 1:9, 2:8, 3:7, and 5:5, pure silicon, and graphite in the voltage range of 0.005-1.5V at 0.1C: the first cycle discharge and charge specific capacities of spherical silicon-carbon composite materials with silicon-carbon ratios of 1:9, 2:8, 3:7, and 5:5 are 696.2mAh / g and 634.6mAh / g, 1012mAh / g and 946.2mAh / g, 1325.9mAh / g and 1238.8mAh / g, and 1891.5mAh / g and 1763mAh / g, respectively, while those of pure silicon are 3428.96mAh / g and 3177.53mAh / g, while those of graphite are only 355.63mAh / g and 333.49mAh / g. The presence of silicon nanoparticles significantly increases the specific capacity of graphite and greatly improves the energy density of lithium-ion batteries. The first coulombic efficiencies are 91.15%, 93.5%, 93.43%, 93.21%, 93.78% (graphite) and 92.67% (pure silicon). Figure 4 It can be seen that the spherical silicon-carbon composite material has an obvious discharge platform when it is close to 0V, corresponding to the alloying of Si and Li. And with the increase of silicon-carbon ratio, that is, the increase of silicon content, its first cycle charge and discharge specific capacity will increase accordingly, and the first efficiency will also increase to a certain extent.
[0090] (4) Table 2 below shows the capacity retention and electrode expansion rate of spherical silicon-carbon composite materials and graphite and pure silicon with silicon-carbon ratios of 1:9, 2:8, 3:7, and 5:5 respectively after 100 charge-discharge cycle tests in the voltage range of 0.005-1.5V:
[0091] Table 2
[0092]
[0093] Figure 5The performance curves of spherical silicon-carbon composite materials and graphite and pure silicon with silicon-carbon ratios of 1:9, 2:8, 3:7, and 5:5 after 100 charge-discharge cycle tests in the voltage range of 0.005-1.5V. The first three cycles were activated at 0.1C, and the subsequent tests were performed at 1C. It can be seen from the figure that after 100 cycles, the remaining discharge specific capacities are 502.9mAh / g, 603mAh / g, 630.3mAh / g, 1068.7mAh / g, 268.85mAh / g (graphite) and 1808.01mAh / g (pure silicon); the capacity retention rates after 100 cycles are 72.23%, 59.58%, 47.54%, 56.5%, 75.6% (graphite) and 52.72% (pure silicon), and after 100 cycles, the corresponding electrode expansion rates are 31.2%, 45.6%, 57.9%, 80.2%, 20.3% (graphite) and 231.5% (pure silicon). It can be seen that when the silicon-carbon ratio is relatively small, that is, when the content of graphite is high, the obtained spherical silicon-carbon composite material has better cycle stability; when the silicon-carbon ratio is relatively large, that is, when the content of nano-silicon is high, the obtained spherical silicon-carbon composite material has a larger specific capacity and a high energy density. The presence of the graphite layer can inhibit the expansion of silicon to a certain extent.
[0094] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.
Claims
1. A method for preparing a spherical silicon-carbon composite material, characterized in that: The preparation method comprises the following steps: Dissolving a binder in a first solvent and performing a first stirring process to obtain a first stirred product; adding graphite to the first stirred product, and performing a second stirring process to obtain a second stirred product; adding a silicon source, a second solvent and a conductive agent to the second stirred product, and performing a third stirring treatment to obtain a third stirred product; The third stirred product is subjected to spray drying treatment to obtain the spherical silicon-carbon composite material, wherein the spherical silicon-carbon composite material includes a spherical structure formed by stacking graphite sheets and silicon bonded to the surface of the spherical structure.
2. The method for preparing the spherical silicon-carbon composite material according to claim 1, characterized in that: The step of dissolving the binder in the first solvent and performing a first stirring process to obtain a first stirred product is specifically: adding the first solvent and the binder into a vacuum stirring kettle, setting the parameters of the vacuum stirring kettle, performing a first stirring process, wherein the time of the first stirring process is 5-150 minutes, and obtaining a first stirred product; Wherein, the parameters of the vacuum stirring kettle include: stirring speed of 20-60rpm, dispersion speed of 300-3000rpm.
3. The method for preparing the spherical silicon-carbon composite material according to claim 1, characterized in that: The step of adding graphite to the first stirred material and performing a second stirring treatment to obtain a second stirred material comprises: adding graphite to a vacuum stirred tank containing the first stirred material, setting parameters of the vacuum stirred tank, performing a second stirring treatment, wherein the time of the second stirring treatment is 5-150 minutes, and obtaining a second stirred material; Wherein, the parameters of the vacuum stirring kettle include: stirring speed of 20-60rpm, dispersion speed of 300-3000rpm.
4. The method for preparing the spherical silicon-carbon composite material according to claim 1, characterized in that: The step of adding a silicon source, a second solvent and a conductive agent to the second agitant and performing a third stirring treatment to obtain a third agitant is specifically: adding a silicon source, a second solvent and a conductive agent to a vacuum stirring kettle containing the second agitant, setting the parameters of the vacuum stirring kettle, performing a third stirring treatment, wherein the time of the third stirring treatment is 5-150 minutes, to obtain a third agitant; Wherein, the parameters of the vacuum stirring kettle include: stirring speed of 20-60rpm, dispersion speed of 300-3000rpm.
5. The method for preparing the spherical silicon-carbon composite material according to claim 1, characterized in that: The parameters of the spray drying process are: inlet temperature of 100-300°C, outlet temperature of 60-120°C, atomizing disk speed of 150-300Hz, and fan frequency of 15-40Hz.
6. The method for preparing the spherical silicon-carbon composite material according to claim 1, characterized in that: In the third mixture, the mass ratio of graphite to silicon source is (3-8):(3-6), the mass ratio of graphite to binder is (95-100):(1-5), and the mass ratio of graphite to conductive agent is (95-100):(1-5).
7. The method for preparing the spherical silicon-carbon composite material according to claim 1, characterized in that: The silicon source is selected from one of nano silicon, micro silicon and porous silicon; the binder is selected from one of CMC binder, PVDF binder and PMMA binder; the conductive agent is selected from one of carbon nanotube, conductive carbon black and graphene; the first solvent is selected from one of water, alcohol and methanol; and the second solvent is selected from one of water, alcohol and methanol.
8. The method for preparing the spherical silicon-carbon composite material according to claim 1, characterized in that: The first stirring process, the second stirring process and the third stirring process are all repeated at least twice.
9. A spherical silicon-carbon composite material, characterized in that: The spherical silicon-carbon composite material comprises a spherical structure formed by stacking graphite sheets and silicon bonded to the surface of the spherical structure; And / or, the spherical silicon-carbon composite material is prepared by the preparation method according to any one of claims 1-8.
10. Use of the spherical silicon-carbon composite material according to claim 9 in the preparation of lithium-ion batteries.
Citation Information
Patent Citations
Preparation method for composite cathode material of lithium ion battery
CN102646818A
Lithium ion battery silicon-carbon anode material and preparation method thereof
CN103367727A
Hollow silicon-carbon composite material for lithium-ion batteries, and preparation method thereof
CN107799728A
